2017
DOI: 10.1111/cen.13289
|View full text |Cite
|
Sign up to set email alerts
|

HLA‐G 3′ untranslated region polymorphic sites associated with increased HLA‐G production are more frequent in patients exhibiting differentiated thyroid tumours

Abstract: HLA-G 3'UTR polymorphisms associated with a greater magnitude of HLA-G production were associated with differentiated thyroid tumours and with variables implicated in poor prognosis. These findings corroborate the unfavourable role of HLA-G in thyroid cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 35 publications
(92 reference statements)
5
17
0
Order By: Relevance
“…Interestingly, +3142G is suggested to increase the binding of miR-148a, miR-148b, and miR-152, suggesting that the allelic variation +3142C found in our cohort of patients might be disadvantageous by impairing binding of regulatory miRs regulatory control in the HLA-G 3′UTR. This is also in line with recent studies, in which the +3142CC genotype was shown to be associated with increased HLA-G levels and susceptibility to cancer 23,52 . Further, it already has been shown that some miRs bind to non-polymorphic sequences of the HLA-G 3′UTR in a stable and specific manner, while others bind to polymorphic sequences.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Interestingly, +3142G is suggested to increase the binding of miR-148a, miR-148b, and miR-152, suggesting that the allelic variation +3142C found in our cohort of patients might be disadvantageous by impairing binding of regulatory miRs regulatory control in the HLA-G 3′UTR. This is also in line with recent studies, in which the +3142CC genotype was shown to be associated with increased HLA-G levels and susceptibility to cancer 23,52 . Further, it already has been shown that some miRs bind to non-polymorphic sequences of the HLA-G 3′UTR in a stable and specific manner, while others bind to polymorphic sequences.…”
Section: Discussionsupporting
confidence: 92%
“…Our comparative haplotype analysis between healthy controls and EOC patients revealed that the overall frequencies of both cohorts are very similar to the ones found in worldwide population studies 25,26,32 . A study of haplotype distribution between papillary thyroid cancer and healthy controls demonstrated significant differences 23 . As we did not observe such differences in HLA-G 3′UTR distribution, this may point to distinct contribution of HLA-G genotypes to the onset of specific forms of cancer or oncological phenotypes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Luo et al demonstrated that overexpression of the CHI3L1 gene was significantly associated with tumor metastasis and reduced OS in patients with thyroid cancer [17]. Also, CLDN10, E2F1, and HLA-G gene expression have been previously reported to be associated with poor survival in thyroid cancer [1820], which are findings that support those of the present study.…”
Section: Discussionsupporting
confidence: 90%